Playwrights for Tomorrow : A Collection of Plays, Volume 13 - Ballet, Arthur H. (Book collections on Project MUSE., 2014)
Playwrights for Tomorrow was first published in 1975. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. Four plays by writers who have worked under the auspices of the Office for Advanced Drama Research (O.A.D.R.) at the University of Minnesota are published in this volume, the thirteenth in the series of such collections. The O.A.D.R. program, which is directed by Arthur H.. Ballet, the series editor, provides an opportunity for promising playwrights to work with cooperating theatres in the production of their plays. The plays in this volume are The Tunes of Chicken Little by Robert Gordon, The Inheritance by Ernest A. Joselovitz, Blessing by Joseph Landon, and The Kramer by Mark Medoff. Three of the plays--those by Robert Gordon, Joseph Landon, and Mark Medoff--were produced by the American Conservatory Theatre of San Francisco. The play by Mr. Joselovitz was presented by the University of Minnesota Theatre in Minneapolis. In his introduction Mr. Ballet comments on the achievements and problems of the O.A.D.R. program. He reports that since the program began it had had about one hundred plays produced in some sixty theatres, not only in the United States but also in Australia, New Zealand, Scotland, and Canada. However, he writes, it became increasingly difficult to find playhouses willing to risk the challenge of new plays and playwrights. "More dangerous still," he writes, "has been the tendency for some directors to make theatre their own, highly personal art. Because so many of these directors only like what they know, and they don't know what to make of new work at all, they cannot truly judge and anticipate as a stage piece anything beyond their immediate ken. The rejections are cavalier and unthinking. The directors' lament that there are no new, exciting playwrights must be answered with the accusation that there really are damned few new, exciting, perceptive directors."